STRATEGI KEPALA SEKOLAH DALAM MENGATASI KEKURANGAN TENAGA PENDIDIK DI SMP ISLAM MA’ARIF SANGATTA UTARA - Yasin, Muhammad; Fadilah, Kiki (MPI STAI Sangatta Kutai Timur, 2023)
Strategy means careful planning of activities to achieve specific goals. The term strategy comes from the Greek strategy which is defined as